FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Suhandy , Ricky; Rasyid, Rosmita (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to examine the effect of leverage, profitability, liquidity, cash flow and dividend payment on cash holding in manufacturing companies listed on the Indonesia Stock Exchange during the year 2017 to 2020. The research used 38 manufacturing companies that were selected using purposive sampling method for a total of 152 sample in four years. The result of the research are profitability have significant positive impact on cash holding, liquidity have insignificant positive impact on cash holding and leverage, cash flow, dividend payment has insignificant negative impact on cash holding.